UNIDIRECTIONAL BRAKING ENERGY RECOVERY SYSTEM FOR ELEVATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The paper discusses design of energy storage based energy recovery system for elevators. The main element of such system is unidirectional DC-DC converter to control energy flow to supercapacitor or li-ion battery based energy storage. The paper gives explanation of selection of the converter topology and some design considerations. The test results of experimental prototype on a developed test bench are presented in the paper.